Efektivitas Pembelajaran Matematika Tentang Penjumlahan 0-100 Menggunakan Media Pembelajaran Kotak Berhitung Braille pada Siswa Kelas Vi Tunanetra di SLB Negeri Kanatang - Ndapatamu, Frans Huma; Selan, Ot Bil Wilson; Wangge, Vinsesnsius; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the effectiveness of Braille counting boxes in improving the ability of visually impaired sixth-grade students at Kanatang State Special School to add numbers between 0 and 100. The background of this study stems from the low mathematics learning outcomes of visually impaired students due to the abstract nature of numerical concepts, which necessitates concrete and tactile learning media to aid understanding. The research used the Classroom Action Research (CAR) method with a single subject design and involved a sixth-grade visually impaired student, Evan Clief Kaka (ECK), with a minimum passing grade (KKM) of 75%. The results showed a clear improvement after the intervention using the Braille Counting Box. The student's initial ability in the pre-action was only 35%, then increased to 50% in the post-test of Cycle I, and reached 80% in the post-test of Cycle II, which exceeded the MCC. Observations also noted an increase in the student's fine motor skills and independence, from the adequate category in Cycle I to the good category in Cycle II. Based on these findings, it can be concluded that the Braille Counting Box is effective in improving the ability to add numbers 0–100 and helps blind sixth-grade students at Kanatang State Special School achieve learning completeness.